Colorado Literacy Tutor jako pomoc w nauce i doskonaleniu czytania w jezyku angielskim dla polskich dzieci - Juszczyk, Konrad (Investigationes Linguisticae, 2005)
The article below is a short presentation of Colorado Literacy Tutor (CLT ) to Polish readers. CLT is a computer program built to help children in developing literacy skills in English. The main advantage of CLT is the deployment of animated highly interactive interface that enhances both human-computer interaction and the student’s learning performance. Designed to help American children, CLT is capable to serve as a learning tool for all children who need to practice reading in English. Since teaching English to Polish children is common in almost all elementary schools and some kindergartens, CLT provides an ideal test bed for research on how Polish children acquire reading abilities in English. The main components of CLT are presented and their impact on reading acquisition is explained. A short preliminary report on author’s pilot study is also given.